Annesang (Muzara'ah) Based on Maslahah and CIBEST in Improving Farmer Welfare in Bulukumba Regency - Sri Nurul Nabila; Rahman Ambo Masse; Sumarlin; Arsyad, Kamaruddin; Abdul Wahab (LP2M IAIN Palopo, 2025)
This study focuses on the implementation of the Annesang (Muzara'ah) system based on the Maslahah concept to improve the welfare of farmers in Batulohe Village, Bulukumpa District, Bulukumba Regency. The phenomenon of profit-sharing cooperation between landowners and rice farmers is important because of income inequality and the risk of injustice in the distribution of harvests, and highlights the spiritual aspect that has so far received little attention. This study uses a qualitative phenomenological approach with observation methods, in-depth interviews, questionnaires, and documentation of 30 farmers. The CIBEST (Center of Islamic Business and Economic Studies) model is used as a multidimensional measuring tool that assesses welfare and poverty from a comprehensive material and spiritual aspect. The results of the study indicate that the implementation of the Maslahah-based Annesang (Muzara'ah) system and the CIBEST model significantly improved the welfare index of farmers in Batulohe Village, particularly in terms of higher income, economic resilience, spiritual satisfaction, and a more balanced quality of life. Challenges encountered included the implementation of oral contracts, unclear capital participation, and risk management that requires a more professional and legal approach. The implications of the study emphasize the importance of strengthening the Maslahah-based Annesang system as a model for fair, sustainable agricultural cooperation, and integrating the spiritual values ​​of agrarian communities. The CIBEST model is recommended as a holistic welfare evaluation instrument that facilitates the formulation of integrated economic and socio-spiritual intervention policies and programs. Regulatory support, facilitation of contract legalization, farmer capacity building, and legal protection by the government and related institutions are expected to ensure that this profit-sharing practice runs effectively, transparently, and is able to improve the welfare of the community as a whole